THE ARABIC TEACHING APPROACHES TO NON-NATIVE SPEAKERS: A BIBLIOMETRIC ANALYSIS - Maimanah Samsuri; Siti Aisyah Mazlan; Tengku Nazatul Shima Tengku Paris; Natasha Zuhaimi (Journal of Islamic, Social, Economics and Development, 2023)
The article aims to conduct a bibliometric analysis using VOSviewer software on a literature review approach to teaching Arabic to non-native speakers. The analysis focuses on data from 2010 to 2023, offering a comprehensive overview of the field and identifying significant trends based on citation patterns, affiliations, authors, and countries. This study encompasses three distinct bibliometric studies to identify the notable scholarly papers, authors, research institutions, geographic regions, and research issues that have significantly influenced Arabic language teaching methodologies. The study utilises bibliometric analysis to examine the association between keywords and the identified research gap. Additionally, noteworthy alterations in the keyword analysis and emerging trends within the field are observed.